The Effectiveness of the Bundo Andini Program in Increasing the Number of Visits by Young Children to the Proklamator Bung Hatta Library In - Vadila Yulia Saputri; Marlini (Darul Yasin Al Sys, 2026)
Book-reading and storytelling programs are increasingly implemented in libraries to promote early literacy; however, their effectiveness in encouraging library visits among young children remains insufficiently examined. This study evaluated the effectiveness of the Bundo Andini Program in increasing visits by young children to the Proklamator Bung Hatta Library in Bukittinggi. A quantitative approach with a descriptive survey design was employed. The population comprised 150 program participants, from whom 60 parents, guardians, and teachers were selected through purposive sampling. Data were collected using a four-point Likert-scale questionnaire and analyzed through frequency distributions, percentages, and mean scores. The findings showed that the Bundo Andini Program achieved an overall mean score of 3.27 and was classified as highly effective. Participant involvement obtained the highest mean score of 3.34, followed by participant satisfaction at 3.31 and program impact at 3.27. Implementation quality received the lowest mean score of 3.18, although it remained within the high category. These findings indicate that the program created an engaging literacy experience, strengthened children’s participation, increased their interest in books, and encouraged repeat library visits. The study concludes that the Bundo Andini Program is an effective library-based literacy initiative for young children. The findings provide practical implications for public libraries to diversify storytelling materials, learning media, and participatory activities to sustain children’s engagement and encourage continued library use.